2017
DOI: 10.1002/mnfr.201700128
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolic alterations induced by genetic ablation of 4E-BP1 and 4E-BP2 in response to diet-induced obesity

Abstract: These findings indicate that 4E-BP proteins may prevent excess lipid accumulation in skeletal muscle and suggest that 4E-BPs are key regulators of muscle homeostasis regardless of insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 56 publications
6
17
2
Order By: Relevance
“…In the present study, using EDL muscles, we observed that protein synthesis was increased under basal conditions and after stimulation with a mix of leucine and insulin in 4E‐BP1/2 DKO mice. This result is in line with previous results where global protein synthesis was found to be increased in vitro in 4E‐BP1/2 DKO haematopoietic stem cells and primary fibroblasts . In another study using 4E‐BP1/2 DKO mice, Steiner et al .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, using EDL muscles, we observed that protein synthesis was increased under basal conditions and after stimulation with a mix of leucine and insulin in 4E‐BP1/2 DKO mice. This result is in line with previous results where global protein synthesis was found to be increased in vitro in 4E‐BP1/2 DKO haematopoietic stem cells and primary fibroblasts . In another study using 4E‐BP1/2 DKO mice, Steiner et al .…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, it was observed that deletion of 4E‐BP1 and 4E‐BP2 resulted in reduced energy expenditure, whereas energy expenditure is unaltered in the present study. An important difference between these previous studies and the current one is the age of the mice (24 vs. 6 months), and this difference might in part explain the absence of modification of energy expenditure we are observing.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations